Gambling careers: A longitudinal, qualitative study of gambling behaviour. (October 2013) - Reith, Gerda; Dobbie, Fiona
<x xml:space="preserve">Abstract</x> This article presents findings from a five year study of 'gambling careers' designed to explore the ways that individuals move in and out of problematic behaviour over time. A longitudinal qualitative methodology was used to investigate patterns of stability and change in a cohort of 50 problem and recreational gamblers. The study found that change, rather than stability, was the norm in gambling behaviour and identified four different trajectories of behaviour: progression, reduction, consistency and non-linearity. Drawing on rich narrative accounts of respondents' gambling behaviour, the study begins to suggest reasons for these different types of movement, highlighting the role of material factors such as employment, environment and social context in each. It concludes that gambling behaviour is highly variable over time, and recommends that future research focus on patterns of behaviour rather than on 'types' of gamblers.